Entre a teoria e a prática: um estudo histórico-etnográfico da metodologia de ensino do Ballet desenvolvida na Escola de Dança Ballare - COUTINHO, Lucienne Ellem Martins (2018)
The present study is linked to the Anthropological Circle of Dance (CIRANDA), research project on which I am scholar of Scientific Initiation (PIBIC/UFPA). In this work I have objected fixing in researchable forms the Royal Academy of Dancing (RAD) method of teaching Classical Ballet, at Ballare’s School of Dance, in Belém, State of Pará, Brazil. The strategies and methodological proceedings of this research were being configured along this trajectory, according to the following moments: theoretical-intellectual phase, marked by lectures of books, articles, thesis and dissertations; practical-experimental phase, in which I have exercised the “participating-observation” of Ballet classes; applied the semi-structured interviewing with ballerinas, teachers and the director of the School, I have transcript the interviews and I have done the analysis of collected data. And, finally, the academic competence phase, which corresponds to the writing and defense of this Work of Conclusion of Course. I start describing the history of Classical Dance in Brazil, since the entering of Classical Dance in Rio de Janeiro, until its arriving in Belém, State of Para. I conceptualize the techniques brought to the country, describing the trajectory of teaching of Classical Dance as well as mentioning the educators and methods that have enabled the diffusion of the classical technic in the city. Finally, I enter in the universe of Ballare’s School of Dance, describing (Ethnography) a whole Ballet class and trying to understand the process of teaching/learning of Classical Dance.